2014
DOI: 10.1537/ase.140827
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary interpretation of the modern human-like facial morphology of the Atapuerca Gran Dolina-TD6 hominins

Abstract: The Early Pleistocene human fossil remains recovered from the TD6 lithostratigraphic unit of the Gran Dolina cave site in the Sierra de Atapuerca, northern Spain, show a mosaic of primitive and derived features. Among the latter, the modern human-like midfacial topography, as well as several synapomorphies shared with some European Middle Pleistocene hominin and Neanderthals, represents a challenge for the phylogenetic interpretation of Homo antecessor. Using an ontogenetic approach of the maxilla ATD6-69, Fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
(69 reference statements)
0
3
0
Order By: Relevance
“…Bermú dez de Castro & Martinó n-Torres [106] concluded that antecessor was a side-branch of a lower Pleistocene radiation of lineages in Eurasia that eventually gave rise to Neanderthals in Europe and to H. sapiens in Africa. If heidelbergensis (sensu Stringer [25]) is not the LCA for sapiens and neanderthalensis because of a derived facial morphology and because the known fossils post-date the actual divergence date, then what did the LCA look like (Ancestor X in figure 2c).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bermú dez de Castro & Martinó n-Torres [106] concluded that antecessor was a side-branch of a lower Pleistocene radiation of lineages in Eurasia that eventually gave rise to Neanderthals in Europe and to H. sapiens in Africa. If heidelbergensis (sensu Stringer [25]) is not the LCA for sapiens and neanderthalensis because of a derived facial morphology and because the known fossils post-date the actual divergence date, then what did the LCA look like (Ancestor X in figure 2c).…”
Section: Discussionmentioning
confidence: 99%
“…For some, this morphology in a fossil dated at more than 800 ka may reflect the ancestral condition for H. sapiens [29]. Previously [2], I questioned whether this morphology would have been maintained in the adult, and whether there would have been population variation in its expression, but it does seem to be expressed in three more fragmentary subadult and adult specimens from Gran Dolina [106]. Issues have also been raised about allometric effects on the zygomaxillary area such that larger archaic faces would show an inflated maxillary morphology more like that of the massive Bodo and Petralona crania [107].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation